Distributed computing and broadband networks: can health professionals get their act together?... this paper was delivered in the first plenary session at the Second National Health Informatics Conference -- HIC '94. - Barbagallo D (Informatics in Healthcare Australia, 1994)
This paper was delivered in the first plenary session at the Second National Health Informatics Conference -- HIC '94. Due to time constraints, it was not included in the Conference Proceedings and is reproduced here verbatim for the first time.